YUNUS DAN BELAS KASIHAN ALLAH: ANALISIS NARATIF YUNUS 4 - Petra Harys Alfredo Tampilang; Anon Dwi Saputro; Farel Yosua Sualang (Phronesis: Jurnal Teologi dan Misi, 2024)
This study aims to investigate and analyze aspects of mercy reflected in the narrative of Jonah 4, with a particular focus on the comparison between God's mercy and Jonah's mercy. Using a narrative literary approach, this study explores the deeper meanings in the text and details Jonah's response to God's mercy as presented in chapter 4. The research method involves literary analysis and identifying narrative elements that reflect the theme of mercy. The center of attention of this study lies at the beginning of the narrative in Jonah 4, where Jonah shows an upset reaction to God's decision to spare Nineveh. Understanding God's mercy and Jonah's response to it is the main focus of the analysis. The findings show a significant difference between God's mercy, which involves His universal love for all nations, and the lack of mercy shown by Jonah towards the Ninevites. The contribution of the findings lies in a deeper understanding of Jonah's character, the dynamics of the relationship between humanity and divinity, and the theological implications contained in the text of Jonah 4.